Anti-tumor effects of the peptide TMTP1-GG-D(KLAKLAK)(2) on highly metastatic cancers. - Xiangyi Ma; Ling Xi; Danfeng Luo; Ronghua Liu; Shu Li; Yan Liu; Liangsheng Fan; Shuangmei Ye; Wanhua Yang; Shuhong Yang; Li Meng; Jianfeng Zhou; et al. (PLoS ONE, 2012)
The treatment of cancer such as oligonucleotides or peptides requires efficient delivery systems. A novel peptide, TMTP1, previously derived and identified in our laboratory showed remarkable ability to target highly metastatic tumors both in vitro and in vivo, even at the early stage of occult metastasis foci. TMTP1 moderately inhibited tumor cell viability, although not enough to deem it an efficient killer of tumor cells. In this study, we sought to enhance the anti-tumor activity of TMTP1. To do this, we fused it to an antimicrobial peptide, (D)(KLAKLAK)(2), and termed the resulting peptide TMTP1-DKK. We found that TMTP1-DKK could trigger rapid apoptosis in human prostate and gastric cancer cells through both the mitochondrial-induced apoptosis pathway and the death receptor pathway. Furthermore, direct injection of TMTP1-DKK into mice with prostate and gastric xenograft cancers resulted in reduction of tumor volumes and a significant delay in tumor progression and metastasis in vivo. These results suggest that TMTP1-DKK may serve as a powerful therapeutic agent for metastatic tumors.